'You're doing everything just fine': Praise in residential care settings. (February 2016) - Jansson, Gunilla
This study examines the use of praise in caregiving of nursing home residents with dementia in Sweden. The data consist of video-recordings of staff–resident interaction in residential care settings where caregivers assist residents with personal hygiene. High-grade assessments accomplishing praise or a compliment such as ' jättebra ' ('great') are routinely used online, simultaneously with the care activity, by the caregiver when the residents are requested to undertake manual tasks on their own, such as tooth brushing, washing, dressing, and getting out of bed. It is shown that the primary function of the assessments is to encourage someone to do something, which is discussed as an institutionally related problem. These results contrast with prior research on domiciliary care in Sweden and Denmark, which show that high-grade assessment terms formulated so as to accomplish praise or a compliment are reserved for situations where the home helper's institutional role as the senior citizen's helping hand is downplayed. It is argued that a more sensitive use of assessments and a higher awareness of the social norms concerning epistemic primacy may be a step toward implementing person-centeredness in residential care for older people.